What role does consumption play in the green deal? - Szubska-Włodarczyk, Natalia (W poszukiwaniu zielonego ładu, 2022)
The chapter deals with the greening of consumption. Considerations include critical analysis of the literature, presentation of case studies and new trends that are making consumption greener. In the European Green Deal, issues related to consumption have been raised many times and relate to various spheres of purchasing activity of households, such as the transition to clean energy, involvement in circular economy, activities provided for in the “Farm to Fork” strategy. Success in the greening of consumption requires appropriate education and institutional support.